El rol de la familia en la atención de niños con trastorno espectro autista en educación básica superior - Monje Santana, Jorge Andrés (2021)
The arrival of a child in the family is a reason for great happiness; But when the child is born with some type of disability, multiple concerns, challenges and uncertainties are generated that are difficult to resolve early. In the case of children with Autism Spectrum Disorders, due to their characteristics, together with their parents' ignorance, it is very complex to attend to them properly Objective. Develop a System of Workshops for the guidance, counseling and support of parents of children with Autism Spectrum Disorders, included in Higher Basic Education. Methodology. The research followed a mixed, descriptive, field approach, with the use of theoretical and empirical methods and techniques such as the survey, interview and documentary review………..